STRATEGIC POSITIONING OF PRODUCTS OF AGRICULTURAL ENTERPRISES IN THE CONDITIONS OF COMPETITION - ODINTSOV, Oleh; PEPCHUK, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the problem of strategic positioning of products of agrarian enterprises in conditions of competition. The global and domestic experience of strategic positioning is analyzed. General definitions of the "positioning" category are given. The main components of positioning are highlighted: idea, strategy and implementation of the plan. The main features of positioning as an idea, as a strategy and as a set of certain practical actions are proposed. The importance of diversification as one of the effective elements of marketing strategies is substantiated.On the basis of the studied author's methodical approaches of marketing classics regarding the strategy of positioning enterprises in the conditions of competition, a certain plan for developing the concept of strategic positioning is proposed, namely: research; quest; justification; programming; correction.It was determined that elements of marketing strategies are at the basis of positioning, in particular: diversification, market segmentation, cooperation, globalization, differentiation, specialization, cost reduction.Diversification is an important element of the company's marketing strategy. Using diversification as a strategy to improve the enterprise, the problem of expanding the types of activities and protection against economic risks of this enterprise is solved. The enterprise strives to develop and manufacture new types of products using the same technology and available resources. The goal of diversification is to increase the company's stability and competitiveness on local and global markets.The study showed that solving the problem of strategic positioning of the products of agrarian enterprises is one of the priority directions of the development of strategic marketing of the enterprise. Positioning determines the development of the enterprise in the long term and the nature of its relations with interested parties.
Keywords: marketing; product; strategic positioning; competitive strategy; marketing strategy